Alameda County State College Bulletin 1962-63 - Alameda County State College:::::: (Alameda County State College; California State Printing Office, 1962)
A catalog of courses offered by State College for Alameda County for the academic year 1962-1963. Includes academic calendar, history of the college, names of faculty and administrators, and descriptions of courses and degrees offered.